Energy utilization and requirement of broiler breeders during the production phase - Teofilo, G. F.S. [UNESP]; Riveros, R. L. [UNESP]; Leme, B. B. [UNESP]; Camargos, R. S. [UNESP]; Macari, M. [UNESP]; Fernandes, J. B.K. [UNESP]; Sakomura, N. K. [UNESP] (Elsevier, 2023)
This study aimed to evaluate energy utilization and propose models for metabolizable and net energy requirements in broiler breeders during the egg production phase. Sixty Cobb500 broiler breeders aged between 29 and 65 wk were randomly assigned to 3 feeding levels. At each age, 6 birds were adapted for 8 d to 3 levels of metabolizable energy intake (MEi), established based on the amount of feed allocated: 1) the amount of feed recommended in the guideline, 2) 25% above, and 3) 25% below. The birds were housed in respirometry chambers for 6 d (1 adaptation, 4 feeding state, 1 fasting) to measure oxygen consumption and carbon dioxide production to calculate heat production (HP) and fasting HP (FHP). Daily measurements of feed intake, egg weight, egg production, and total excreta were recorded. Variables of MEi, HP, and retained energy (RE) in the egg were calculated, while RE in the body and its partitioning into fat and protein in the egg and body were calculated from MEi, total HP (THP), and RE in the egg. Statistical analysis involved linear regression of multiple factors with MEi and age (categorical) as the independent variables. Pearson correlation analysis was conducted to investigate the relationship between visceral mass and the evaluated variables. The study proposed mixed models for developing models of energy requirements for both metabolizable (ME) and net systems (NE). The study found that FHP (average 259 ± 20.08 kJ/kg0.75*d) remained constant throughout the production cycle regardless of the MEi level (P > 0.05). The efficiency of energy utilization for depositing protein and fat in the body changed with the bird's age. The lower error model was considered to select ME requirements for maintenance, egg, and gain efficiencies, disregarding the effect of age. The efficiencies were 0.89, 0.78, and 0.80 for maintenance, gain, and egg production, respectively. The NE was unaffected by age and showed a lower error than the ME model. The NE system was found to be more accurate in expressing the energy requirements of broiler breeders.
Keywords: energy balance; energy retention; fasting heat production; heat production; indirect calorimetry